NEW CHALLENGES FOR AUDITORS IN FORMING AN OPINION AND DISCLOSING INFORMATION ON THE MANAGEMENT REPORT OF FINANCIAL STATEMENTS OF BANKS - Socol, Adela (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 19 (2017): Annales Universitatis Apulensis Series Oeconomica, 2017)
In the last years improving disclosure effectiveness has become a priority issue in financial reporting of banks. The purpose of this paper is to explore ways to improve financial reporting disclosure studying auditors' attitude in forming an opinion on Management report of banks (Administrators' report). First three banks by assets size from Romania were studied in order to identify the differences and similarities between format/structure and contents of Management report of banks, based on the financial statements for the financial period that ended on 31 December 2015. The focus is on auditors' professional judgment in determining the most adequate considerations and concerns when expressing their opinion on financial statements based on Management report of audited entity. We analysed the banks' options in adopting a proper format and structure of management report and in making materiality assessments through management report. The paper shows the differences in the studied banks' Management reports, the standardized form of auditors' opinion regarding to Management report of banks and doubts about not fully understandability by users of financial statements.